Life cycle assessment of agricultural waste recycling for sustainable environmental impact - S. Sumiyati; B.P. Samadikun; A. Widiyanti; M.A. Budihardjo; S. Al Qadar; A.S. Puspita (Global Journal of Environmental Science and Management)
Agricultural waste recycling is crucial for sustainable farming operations and farming practices. Life cycle assessment has emerged as an innovative and comprehensive viewpoint that considers the entire recycling process to evaluate the potential and true implications of agricultural waste recycling. This study considered methods for recycling different agricultural waste streams, such as crop waste, animal manure, pruning materials, and by-products and subsequent uses. Furthermore, the life cycle assessment method was used to investigate the process of handling agricultural waste, from collection and recycling to final usage in the agricultural system. Environmental impact categories, including greenhouse gas emissions, energy usage, eutrophication, acidification, and land use, were evaluated to determine their potential effects on climate change, resource depletion, and ecosystem health. The results were compared with those of 31 studies that analyzed the potential environmental impacts of agricultural waste management. Various methods initially developed and implemented for agricultural waste landfilling methods have now changed to energy-generating sources, such as biochar, biogas, briquettes, and various energy production methods. Furthermore, composting, a popular method of recycling agricultural waste, significantly lowers greenhouse gas emissions and energy use compared to traditional waste disposal techniques. The study also examines cutting-edge technologies, such as anaerobic digestion and biomass-to-energy conversion, highlighting their potential to manage agricultural waste and being a sustainable energy source. These findings indicate potential environmental advantages in terms of decreased greenhouse gas emissions and fossil fuel consumption, leading to a circular economic approach for agriculture. When integrating agricultural waste, including composting, anaerobic digestion, and pyrolysis, biochar is highlighted as a waste recycling method that is promising for sustainable waste management. In addition to efficiently managing agricultural waste, these technologies help generate electricity and sequester carbon, thereby advancing the objectives of climate change mitigation and circular economy. Although life cycle assessment has been used to analyze several waste management strategies, including those specific to agricultural waste, certain significant gaps and discoveries still require attention for a more thorough analysis. It might be challenging to gather complete and accurate data to assess the entire lifecycle of agricultural waste management technology. The direct environmental effects of waste management are frequently the focus of life cycle assessment studies, but they may overlook secondary effects such as indirect land use change, habitat damage, and biodiversity effects. It is crucial to consider these secondary effects in a more comprehensive analysis.